2011
DOI: 10.5009/gnl.2011.5.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Papillary Balloon Dilation for Removal of Choledocholithiasis: Indications, Advantages, Complications, and Long-Term Follow-Up Results

Abstract: Endoscopic papillary balloon dilation (EPBD) is an alternative method of endoscopic sphincterotomy (EST). Although concerns regarding post-procedure pancreatitis have been expressed, EPBD has come to be recognized as an effective and safe method for stone removal in specific cases. To analyze the proper indications, ideal methods, complications, and long-term follow-up results for EPBD, we reviewed articles about EPBD located through a search of the PubMed data base. We analyzed the ballooning methods, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9]11,12,15 EPBD and subsequent stone removal generally cleared the bile duct in 79% to 100% of patients in published studies. 1,3,4,[7][8][9][10][11] Our complete bile duct clearance rate was 91.6% (273/298).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9]11,12,15 EPBD and subsequent stone removal generally cleared the bile duct in 79% to 100% of patients in published studies. 1,3,4,[7][8][9][10][11] Our complete bile duct clearance rate was 91.6% (273/298).…”
Section: Discussionmentioning
confidence: 99%
“…It has gained popularity outside the United States 4 and, since 1983, it has been a safe and effective alternative to EST for removing CBD stones. [3][4][5][6] Although a high incidence of acute pancreatitis (4.3% to 19.8%) after this procedure has been reported in most published studies. [1][2][3][4][5][6][7][8][9][10] This technique was further reevaluated and reported that the pancreatitis complication rates of EPBD were similar to those of EST.…”
mentioning
confidence: 99%
“…First, EPBD results in less trauma to the ampullary sphincter. Second, EPBD might preserve the function of the biliary sphincter [2] , reducing late complications such as the recurrence of biliary stones [23,24] . Third, EPBD has the advantage of less bleeding and is safer for patients with bleeding tendency.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic characteristics of the 153 patients cedure-related death (0.4%) [2] . EPBD has become an alternative to EST for the treatment of CBD stones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation